Pengaruh Mental Siswa terhadap Pembelajaran Passing Bawah Bola Voli dan Strategi Peningkatannya Kelas VII MTs SA Atholibiyah Bumijawa - Isroi Isroi; Ramdhani Rahman (Mutiara Pendidikan dan Olahraga, 2025)
This study aims to determine the extent to which mental ability influences volleyball underhand passing skills and strategies for improving them in seventh-grade students at MTs SA Atholibiyah Bumijawa. The mental abilities studied included learning motivation, concentration, and self-confidence, as all three are considered important factors in supporting sports performance. The study used an experimental survey method with a correlation approach. The sample was determined through a purposive sampling technique, meaning only students who were actively involved in volleyball learning were included as respondents. The research instruments included a questionnaire to measure students' mental ability levels and an observation sheet to assess underhand passing skill practice. Data analysis was conducted using a correlation test to identify the relationship between mental ability and underhand passing skills, and regression analysis to measure the magnitude of the effect. The results showed a significant effect of mental ability on underhand passing skills. Students with high learning motivation tend to be more enthusiastic and consistent in practicing. Good concentration enables students to control movements, maintain balance, and manage timing when passing. In addition, strong self-confidence encourages students' courage in making decisions and reduces technical errors. This results in passing skills with more accuracy, control, and optimal timing. Improving strategies that can be implemented include structured training with the use of assistive devices to enhance technique, providing motivation and positive feedback from teachers to maintain enthusiasm, and focused training such as game simulations to strengthen concentration. The findings of this study confirm that mental development plays a crucial role in learning sports skills, particularly volleyball, thereby improving both the quality of learning and student achievement.